Genomic analysis of ctx-m-group-1-producing extraintestinal pathogenic e. Coli (expec) from patients with urinary tract infections (uti) from colombia (2021)
Background: The dissemination of the uropathogenic O25b-ST131Escherichia coliclone constitutes a threat to public health. We aimed to determine the circulation ofE. colistrains belonging to O25b:H4-B2-ST131 and theH30-Rx epidemic subclone causing hospital andcommunity-acquired urinary tract infections (UTI) in Colombia. Methods: Twenty-six nonduplicate,CTX-M group-1-producing isolates causing UTI in the hospital and community were selected for thisstudy. Results: Twenty-twoE. coliisolates harboring CTX-M-15, one CTX-M-3, and three CTX-M-55were identified. Multilocus Sequence Typing (MLST) showed a variety of sequence types (STs), amongwhich, ST131, ST405, and ST648 were reported as epidemic clones. All theE. coliST131 sequencescarried CTX-M-15, from which 80% belonged to the O25b:H4-B2 andH30-Rx pandemic subclonesand were associated with virulence factorsiss,iha, andsat.E. coliisolates (23/26) were resistant tociprofloxacin and associated with amino acid substitutions in quinolone resistance-determining regions(QRDR). We detected two carbapenem-resistantE. coliisolates, one coproducing CTX-M-15, KPC-2,and NDM-1 while the other presented mutations inompC. Additionally, one isolate harbored thegenemcr-1. Conclusions: Our study revealed the circulation of theE. coliST131, O25b:H4-B2-H30-Rxsubclone, harboring CTX-M-15, QRDR mutations, and other resistant genes. The association of theH30-Rx subclone with sepsis and rapid dissemination warrants attention from the public health andinfections control.